Leadership and knowledge management in an e-government environment - Sherry D. Ryan; Xiaoni Zhang; Victor R. Prybutok; Jason H. Sharp (Administrative Sciences, 2012)
The Malcolm Baldrige National Quality Award (MBNQA) is well known to assess quality and business processes in a variety of sectors, including government. In this study, we investigate the relationship between aspects of the MBNQA's leadership triad and knowledge management in an e-government context. Specifically, we survey 1,100 employees of a medium-sized city government in the United States to investigate the relationship between leadership triad components, leadership strategic planning, and customer/market focus, with knowledge management. Our results show that these components are significantly related to knowledge management and are important in the delivery of e-government applications to the citizenry.
Keywords: 350; e-government; knowledge management; leadership strategic planning; customer and market focus; The Malcolm Baldrige National Quality Award; MBNQA